Learning Content of Islamic Education Based on Multikultural in Senior High School in Bandar Lampung - Pahrudin, Agus; Syafril, Syafrimen; Sada, heru Juabdin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2018)
This study aims to describe how Multicultural Content-Based Islamic Educational Content. The research is run using a descriptive-qualitative approach (multi-case multi-site). The data were collected through in-depth interviews to two experts of Islamic education and focus group interviews to four teachers who have had work experience of seven to twenty years. Furthermore, the data were analyzed qualitatively using NVIVO 10.0 software. The results of the research show that the content of Islamic-Based Multicultural Education Learning is: Explaining the concept of aqidah and muamalah, Designing material by applying multicultural and emphasizing on equality principle, Making culture as Content, and Rahmatalillalamin Islam concept.